Immunity, Inflammation and Heart Failure: Their Role on Cardiac Function and Iron Status - Perticone, Maria; Zito, Roberta; Miceli, Sofia; Pinto, Angelina; Suraci, Edoardo; Greco, Marta; Gigliotti, Simona; Hribal, Marta Letizia; Corrao, Salvatore; Sesti, Giorgio; Perticone, Francesco (Frontiers in Immunology, 2019)
Aims. Heart failure is a clinical syndrome characterized by subclinical systemic inflammation and immune system activation associated with iron deficiency. No data exist about a different activation of immune-mediated inflammation in heart failure patients with reduced/preserved ejection fraction. We aimed to 1)investigate possible differences in immune-mediated inflammatory parameters and oxidative stress, 2) detect a different iron status between groups. Materials and Methods. We enrolled 50 consecutive Caucasian outpatients with a diagnosis of heart failure. All patients underwent echocardiographic measurements, laboratory determinations, evaluation of iron status and of Toll-like receptors and NF-kB expression, as well as of pro-inflammatory cytokines. All statistical calculations were made using SPSS for Mac version 21.0. Results. Patients with reduced ejection fraction showed significantly lower haemoglobin levels (12.3±1.4 vs 13.6±1.4 g/dl), serum iron (61.4±18.3 vs 93.7±33.7 mcg/dl), transferrin iron binding capacity (20.7±8.4 vs 31.1±15.6 %), and e-GFR values (78.1±36.1 vs 118.1±33.9 ml/min*1,73 m2) in comparison to patients with preserved ejection fraction, while unsatured iron binding capacity (272.6±74.9 vs 221.7±61.4 mcg/dl), hepcidin (4.61±0.89 vs 3.28±0.69 ng/ml) and creatinine (1.34+0.55 vs 1.03+0.25 mg/dl) were significantly higher in the same group. When considering inflammatory parameters, patients with reduced ejection fraction showed significantly higher expression of both Toll-like receptors-2 (1.90+0.97 vs 1.25+0.76 MFI) and Toll-like receptors-4 (4.54+1.32 vs 3.38+1.62 MFI), respectively, as well as a significantly higher activity of NF-kB (2.67+0.60 vs 1.07+0.30). Also pro-inflammatory cytokines, interleukin-1 and interleukin-6, resulted significantly higher in patients with reduced ejection fraction, while the protective cytokine interleukin-10 resulted significantly lower in the same group. Conclusions. Our date demonstrate a different immune-mediated inflammatory burden in heart failure patients with reduced or preserved ejection fraction, as well as significant differences in iron status. These data contribute to further elucidate pathophysiologic mechanisms leading to cardiac dysfunction.